Professional Android 4 Application Developmemt. - Reto Meier (John Wiley & Sons, 2021)
Chapters 1 and 2 introduce mobile development and contain instructions to get you started in Android. Beyond that, there’s no requirement to read the chapters in order, although a good understanding of the core components described in Chapters 3–9 is important before you venture into the remaining chapters. Chapters 10 and 11 cover important details on how to create an application that provides a rich and consistent user experience, while Chapters 12–19 cover a variety of optional and advanced functionality and can be read in whatever order interest or need dictates.